Pengembangan Antarmuka Website E-Learning untuk Meningkatkan Minat Belajar Pemrograman Dasar Dalam Bahasa Pemrograman Java bagi Mahasiswa Fakultas Ilmu Komputer Universitas Brawijaya - Fatur Rahnat Ariyan; Retno Indah Rokhmawati; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Faculty of Computer Science (FILKOM) Universitas Brawijaya is one of the faculties that have studied technology and computers in Indonesia, from the data of respondents I got through questionnaires distributed to 100 FILKOM students there were about 67% thought that programming was important, but 52% of respondents find it difficult to follow learning in the first year of lecture for various reasons, one of which is the lack of reference to relevant learning materials so that this study aims to develop an e-learning website interface for students of the Faculty of Computer Science Universitas Brawijaya using the Goal Directed Design (GDD) method. The GDD method has six stages that provide website development solutions in accordance with user objectives, namely Research, Modeling, Requirements, Frameworks, Refinements, and Support. From the whole process, data obtained that support user needs such as persona and user journey, hierarchical task analysis, wireframe design, high-fidelity prototype, and finally the results of the evaluation. The evaluation process is done by 2 methods, namely user testing and expert evaluation using immersion testing by asking several experts to try the product and provide input. From the user side we get positive and negative inputs such as the use of a simple and easy to understand design, some buttons and information that is less informative, to the use of live coding features that should be given a special page. While on the expert side, the input is in the form of adding debugging flow visualization, to adding interactions in the form of threads on the discussion forum page.